Angular interrogation analysis of metal-dielectric grating metasurfaces for efficient tuning of surface plasmons - Shafeek Abdul Samad; Nityanand Kumawat; Priyamvada Venugopalan; Sunil Kumar (Scientific Reports)
Abstract Plasmonic nanostructures enable tunable control of light emission, propagation, and confinement through engineered resonances. This study presents a comprehensive analysis of angular interrogation in one-dimensional (1D) metal-dielectric grating metasurfaces by systematically tuning opto-geometric parameters to tailor surface plasmon resonance (SPR) characteristics. We investigate the influence of large grating modulation depths (d > 100 nm) and a broad range of grating periods (300–2000 nm) on zeroth-order angular reflection over an angular span of 0° to 89°. Numerical predictions are validated through experimental characterization using commercial optical-disc gratings coated with a 50 nm gold film. We analyze the evolution of SPR band characteristics with grating period and depth, identifying the emergence of both broadband and narrowband angular resonances. Finite Element Method (FEM) simulations reveal reflection dip closures at grating periods of 925 nm and 1250 nm for excitation wavelengths of 633 nm and 850 nm, respectively. The optimized grating configurations yield high-contrast, narrow reflection dips with angular full-width-at-half-maximum (FWHM) < 1.5°, resulting in an order-of-magnitude improvement in the figure of merit (FOM). The originality and impact of this study lie in its systematic and extensive analysis of deep metal-dielectric grating metasurfaces to attain narrow bandwidths, effectively advancing beyond the conventional practice of using shallow modulation depths. Importantly, the results reveal a highly tolerant design space that supports narrowband responses in angular interrogation of 1D grating metasurfaces, enabling scalable, tunable, and high-resolution plasmonic device development across broader geometric and operational regimes than previously achieved.